Polymorph Characterization of Active Pharmaceutical Ingredients (APIs) Using Low-Frequency Raman Spectroscopy. Issue 7 (July 2014) - Larkin, Peter J.; Dabros, Marta; Sarsfield, Beth; Chan, Eric; Carriere, James T.; Smith, Brian C.
Polymorph detection, identification, and quantitation in crystalline materials are of great importance to the pharmaceutical industry. Vibrational spectroscopic techniques used for this purpose include Fourier transform mid-infrared (FT-MIR) spectroscopy, Fourier transform near-infrared (FT-NIR) spectroscopy, Raman spectroscopy, and terahertz (THz) and far-infrared (FIR) spectroscopy. Typically, the fundamental molecular vibrations accessed using high-frequency Raman and MIR spectroscopy or the overtone and combination of bands in the NIR spectra are used to monitor the solid-state forms of active pharmaceutical ingredients (APIs). The local environmental sensitivity of the fundamental molecular vibrations provides an indirect probe of the long-range order in molecular crystals. However, low-frequency vibrational spectroscopy provides access to the lattice vibrations of molecular crystals and, hence, has the potential to more directly probe intermolecular interactions in the solid state. Recent advances in filter technology enable high-quality, low-frequency Raman spectra to be acquired using a single-stage spectrograph. This innovation enables the cost-effective collection of high-quality Raman spectra in the 200–10 cm −1 region. In this study, we demonstrate the potential of low-frequency Raman spectroscopy for the polymorphic characterization of APIs. This approach provides several benefits over existing techniques, including ease of sampling and more intense, information-rich band structures that can potentially discriminate among crystalline forms. An improved understanding of the relationship between the crystalline structure and the low-frequency vibrational spectrum is needed for the more widespread use of the technique.